2020
DOI: 10.24198/jkg.v32i3.27790
|View full text |Cite
|
Sign up to set email alerts
|

<p>Korelasi usia kronologis dengan densitas tulang mandibula pada radiograf panoramik pada pasien perempuan usia 5-35 tahun</p><p>Corellation between chronological age with mandibular bone density on panoramic radiographs of female patients aged 5-35 years</p>

Abstract: Pendahuluan: Tingkat perkembangan dan maturasi seorang pasien tidak dapat diketahui secara pasti dari usia kronologis, dikarenakan adanya variasi waktu percepatan pertumbuhan pubertas pada setiap individu, maka perlu ditentukan usia biologisnya. Usia biologis ini dapat ditentukan dari usia tulang berupa kualitas tulang yang dapat dilihat dari ukuran densitas tulang. Radiograf panoramik dapat menilai kualitas kepadatan (densitas) tulang secara makrostruktur dan mikrostruktur. Penelitian ini menggunakan sampel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
(20 reference statements)
2
4
0
Order By: Relevance
“…This hormone can help to form and maintain bone mass. 2 In this study, it was also found that DBI was mostly found in the age group of 17 to 25 years old. This is because at this age range, bone growth, bone modification, and bone density are still in good condition.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This hormone can help to form and maintain bone mass. 2 In this study, it was also found that DBI was mostly found in the age group of 17 to 25 years old. This is because at this age range, bone growth, bone modification, and bone density are still in good condition.…”
Section: Discussionsupporting
confidence: 64%
“…This is because the greatest increase in trabeculae occurs in adolescence and will decrease during the maturation or adulthood and the bone remodelling in adulthood decreases. 2 In the research conducted by Wang et al regarding changes in the size of DBI, the results indicate that the size of DBI has a tendency to increase during adolescence and is stable or does not change in adulthood. 11 Other factors that can cause DBI are most commonly found in late adolescence or the age group of 17-25 years because at this age, orthodontic treatment is usually carried out, which prioritizes aesthetic reasons or psychosocial factors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The peak bone growth and development in males are known to be higher than in females, characterized by a larger peak growth in males compared to females, which leads to a slower decrease in mandibular cortical thickness in male patients. 10,19,20 The research results in Table 3 indicate that the group with age ≥ 65 years has the lowest average mandibular cortex value compared to other groups, with a value of 0.22 ± 0.06. These findings are consistent with the study by Naik A et al, which states that mandibular cortical thickness values tend to increase with age.…”
Section: Discussionmentioning
confidence: 98%
“…17,18 The development and bone density in women are also known to be greatly influenced by estrogen hormone, and during menopause, when the ovaries stop producing estrogen, it leads to an increase in bone loss. 10,19,20 Women usually have a higher level of compliance in taking amlodipine medication compared to men. This is what leads to a decrease in bone density.…”
Section: Discussionmentioning
confidence: 99%